Development of adaptive filtering algorithm for multi-frequency audiofile - Maslov, Alexey; Lepikhin, Timur (2015 International Conference "Stability and Control Processes" in Memory of V.I. Zubov (SCP), 2015)
The purpose of this paper is to examine various methods of audio file filtering and develop a combination of known methods. LMS-algorithm with specifications is considered. The criteria of audio-filtering are developed. Program implementation for developed algorithm is presented.